2016
DOI: 10.1007/s00251-016-0936-8
|View full text |Cite
|
Sign up to set email alerts
|

Are human iNKT cells keeping tabs on lipidome perturbations triggered by oxidative stress in the blood?

Abstract: The central paradigm of conventional MHC-restricted T cells is that they respond specifically to foreign peptides, while displaying tolerance to self-antigens. In contrast, it is now becoming clear that a number of innate-like T cell subsets-CD1-restricted T cells, Vγ9Vδ2 T cells, and MAIT cells-may operate by different rules: rather than focusing on the recognition of specific foreign antigens, these T cells all appear to respond to alterations to lipid-related pathways. By monitoring perturbations to the "li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 131 publications
0
6
0
Order By: Relevance
“…Meanwhile, CD1-restricted T cells, responded to alterations to lipid-related pathways. Guo et al (2018) found that naive CD4 + T cells was activated after stimulated by CD1c + APC presenting lipids and preferentially expressed TRBV4-1 + TCRs, which was confirmed as CD1c-restricted autoreactivity (Felley and Gumperz, 2016). Studies have shown that bacterial phospholipids can activate CD1-restricted T cells by binding directly to CD1 from antigen-presenting cells and TCRs, which preferentially express TRBV4-1 + TCRs, thus emphasizing a mechanism for CD1-mediated T cell activation to protect against Mtb infection (Kasmar et al, 2011;Van Rhijn and Moody, 2015;Shahine et al, 2017;Guo et al, 2018;Reinink et al, 2019;Tezera et al, 2020).…”
Section: Discussionmentioning
confidence: 84%
“…Meanwhile, CD1-restricted T cells, responded to alterations to lipid-related pathways. Guo et al (2018) found that naive CD4 + T cells was activated after stimulated by CD1c + APC presenting lipids and preferentially expressed TRBV4-1 + TCRs, which was confirmed as CD1c-restricted autoreactivity (Felley and Gumperz, 2016). Studies have shown that bacterial phospholipids can activate CD1-restricted T cells by binding directly to CD1 from antigen-presenting cells and TCRs, which preferentially express TRBV4-1 + TCRs, thus emphasizing a mechanism for CD1-mediated T cell activation to protect against Mtb infection (Kasmar et al, 2011;Van Rhijn and Moody, 2015;Shahine et al, 2017;Guo et al, 2018;Reinink et al, 2019;Tezera et al, 2020).…”
Section: Discussionmentioning
confidence: 84%
“…Regulatory iNKT10 cells are selectively enriched in the AT and rapidly respond to stimulatory lipids presented by CD1d+ macrophages, or adipocytes, by secreting IL-4 that restrains M1 and promotes M2 polarization ( 25 , 35 , 83 , 85 , 86 ). However, a prolonged dysmetabolic state provokes down-regulation of CD1d on AT-M2 cells and their switch to an M1-like phenotype that, in turn, leads also to a pro-inflammatory shift of local iNKT cells ( 83 , 87 , 88 ), again suggesting a plasticity due to the migration of iNKT1 cells from other sites or a functional differentiation of local cells. The presence of iNKT cells in the AT, which is conserved between mouse and human, is crucial for the formation of fat-associated lymphoid clusters (FALC).…”
Section: The Adipose Tissuementioning
confidence: 99%
“…It has become increasingly clear that the immune system has evolved the ability to recognize and respond to changes in various lipid moieties through a number of innate-like T-cell subsets. 17 Chief among these are NK T cells (NKT), which are able to respond to changes in lipid species via their recognition of a wide variety of self and non-self lysophospholipid species bound to the nonclassical MHC molecule CD1D. 18,19 NKT recognition of lipids bound to CD1D has been shown to play a role in controlling immune responses in multiple different contexts including atheroschlerosis, [20][21][22] multiple models of autoimmunity, 23 cancer, 24 as well as bacterial, mycobacterial, and fungal infections.…”
Section: Introductionmentioning
confidence: 99%
“…One potential source of DAMPs is altered endogenous lipids that occur during RBC storage. It has become increasingly clear that the immune system has evolved the ability to recognize and respond to changes in various lipid moieties through a number of innate‐like T‐cell subsets 17 . Chief among these are NK T cells (NKT), which are able to respond to changes in lipid species via their recognition of a wide variety of self and non‐self lysophospholipid species bound to the nonclassical MHC molecule CD1D 18,19 .…”
Section: Introductionmentioning
confidence: 99%